Factors Associated With Financial Relationships Between Spine Surgeons and Industry: An Analysis of the Open Payments Database. Issue 18 (15th September 2017) - Weiner, Joseph A.; Cook, Ralph W.; Hashmi, Sohaib; Schallmo, Michael S.; Chun, Danielle S.; Barth, Kathryn A.; Singh, Sameer K.; Patel, Alpesh A.; Hsu, Wellington K.
Abstract : Study Design: A retrospective review of Centers for Medicare and Medicaid Services Database. Objective: Utilizing Open Payments data, we aimed to determine the prevalence of industry payments to orthopedic and neurospine surgeons, report the magnitude of those relationships, and help outline the surgeon demographic factors associated with industry relationships. Summary of Background Data: Previous Open Payments data revealed that orthopedic surgeons receive the highest value of industry payments. No study has investigated the financial relationship between spine surgeons and industry using the most recent release of Open Payments data. Methods: A database of 5898 spine surgeons in the United States was derived from the Open Payments website. Demographic data were collected, including the type of residency training, years of experience, practice setting, type of medical degree, place of training, gender, and region of practice. Multivariate generalized linear mixed models were utilized to determine the relationship between demographics and industry payments. Results: A total of 5898 spine surgeons met inclusion criteria. About 91.6% of surgeons reported at least one financial relationship with industry. The median total value of payments was $994.07. Surgeons receiving over $1, 000, 000 from industry during the reporting period represented 6.6% of the database and accounted for 83.5% of the total value exchanged. Orthopedic training ( P  < 0.001), academic practice setting ( P  < 0.0001), male gender ( P  < 0.0001), and West or South region of practice ( P  < 0.0001) were associated with industry payments. Linear regression analysis revealed a strong inverse relationship between years of experience and number of payments from industry ( r  = -0.967, P  < 0.0001). Conclusion: Financial relationships between spine surgeons and industry are highly prevalent. Surgeon demographics have a significant association with industry-surgeon financial relationships. Our reported value of payments did not include ownership or research payments and thus likely underestimates the magnitude of these financial relationships. Level of Evidence: 3